The scientometric evaluation of the research on the production of bioenergy from biomass - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of the literature on the production of bioenergy from biomass published during the last three decades, based on the databases of Science Citation Index-Expanded (SCIE) and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques. The results of this study reveal that the research output in this field has grown exponentially during this period reaching to 5892 papers in total with paralleling enormous changes in the research landscape. Papers are mostly journal articles, reviews, and proceedings, being predominantly in English. The US is the most publishing single country producing 27% of the output, but lagging significantly behind the Europe as a whole (near 50%). The "Chinese Academy of Sciences" is the most contributing institution where the most publishing author is "A Demirbas". "Biomass & Bioenergy" is the most publishing journal whilst, "Energy & Fuels" is the most published subject area. The total number of citations is 82,732, giving a ratio for the "Average Citations per Item" as 13.83 and "H-index" as 102. The results of this first-ever such study of its kind show that the scientometric analysis has a great potential to gain valuable insights into the evolution of the research on the production of bioenergy from biomass. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Biomass; Bioenergy; Research evaluation; SCIE; Scientometrics; SSCI